Učinkovito upravljanje časa - upravljanje samega sebe v odnosu do časa - Šarotar Žižek, Simona (Naše gospodarstvo, 2008)
Each day more and more activities are to be performed inside and outside of organisations within a limited time. Therefore, all kinds of staff members often experience a lack of time. We have become aware that time is a "special resource," invisible but finite. We cannot buy time nor get it in some other way; it cannot be stored or transformed. Therefore, it is necessary to use it optimally in order to be productive and successful at work, by reaching goals successfully, increasing personal efficiency, reducing stress, increasing motivation and job satisfaction as well as gaining a balance between work and personal life. We can successfully manage ourselves in relation to time, arranging our time in a way that makes it possible to reach goals that are important to us.
Keywords: management; čas; upravljanje; načrtovanje; organizacija dela; učinkovitost; efficiency